Technological adequacy of sugar beet products used in the food industry - M. I. Egorova; L. N. Puzanova; I. S. Mikhaleva; A. S. Vlasenko (Пищевые системы, 2023)
Beet sugar production in Russia annually gives about 6 million tons of white sugar and 1.5 million tons of beet molasses, which must have technological adequacy, when used as raw materials. The purpose of the work was to substantiate the concept of technological adequacy of beet sugar production, its indicator markers and their threshold values, to assess the actual technological adequacy of white sugar and molasses, to verify the hypothesis about the relationship between individual indicators of white sugar and empirical knowledge about an increase in the content of micronutrients with a decrease in the category. The objects of the study were terminology related to the characteristics of food products and raw materials in terms of consumer expectations and indicators of their assessment. Technological adequacy was evaluated for 230 samples of white sugar and 134 samples of beet molasses. Indicator markers were determined according to standardized and known methods. Technological adequacy of white sugar and beet molasses is the compliance of their specific functional properties with the requirements of the production of a particular food product, in which they are raw ingredients. A measure of compliance is indicator markers in the form of physicochemical parameters of the composition. Indicators of white sugar for three food technologies and indicators of beet molasses for two technologies and storage were substantiated; their technological adequacy was assessed. Empirical knowledge about an increase in the content of micronutrients with a decrease in the category and the hypothesis about the relationship between individual indicators of white sugar were confirmed. It is shown that all white sugar of extra and TC1 categories has technological adequacy for the use in food production, while only 62% of TC2 sugar and some batches of beet molasses have the necessary technological suitability. The results obtained will be a tool for regulating the production of competitive products and developing a control scheme for the technological flow of sugar production.